Silent partner : a memoir of my marriage - McGreevey, Dina Matos (New York : Hyperion, 2007)
It was an unforgettable scene. Dina Matos McGreevey, an attractive woman in her mid-thirties, wife, mother, and First Lady of the state of New Jersey, watched silently as her husband, then Governor Jim McGreevey, resigned his office with the revelation that he was a "gay American." The picture of grace and loyalty, perfectly composed in her pale blue suit, Dina Matos McGreevey gave no sign of the tangled mixture of fear, sorrow, and anger she felt that day, no hint of the devastation that was to come. Since then she has been asked repeatedly about the nature of her marriage, about what she knew and when she knew it. Since then, she has remained silent--until now. Speaking up at last, Matos McGreevey here recounts the details of her marriage. What emerges is a tale of love and betrayal, of heartbreak and scandal, and, ultimately, hope.--From publisher description
Includes index.
Keywords: McGreevey, Dina Matos -- Marriage; McGreevey, James E., -- 1957- -- Marriage; Governors' spouses -- New Jersey -- Biography; Gay men -- Relationships with heterosexual women -- New Jersey